2001
DOI: 10.1210/en.142.10.4540
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Promotes Selective Uptake of High Density Lipoprotein Cholesterol Esters in Bovine Adrenal Glomerulosa and Human Adrenocortical Carcinoma Cells Through Induction of Scavenger Receptor Class B Type I

Abstract: Angiotensin II is one of the main physiological regulators of aldosterone biosynthesis in the zona glomerulosa of the adrenal cortex. The hormone stimulates intracellular cholesterol mobilization to the mitochondrion for steroid biosynthesis. Here we have examined whether angiotensin II also modulates exogenous lipoprotein cholesterol ester supply to the steroidogenic machinery and whether this control is exerted on the selective transport of high density lipoprotein-derived cholesterol ester to intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…The fact that BeWo, a cell line with many characteristics of cytotrophoblast, are almost lacking SR-BI and SR-BI-mediated selective CE-uptake from HDL 3 , supports the assumption that JAr and Jeg3 resembling syncytiotrophoblasts-like properties are suitable in vitro models to study directed cholesterol/CE-transport in polarized cells. Invasiveness of trophoblast cells in vivo and choriocarcinoma cells in vitro apparently is linked to celldifferentiation and proliferation [47] similar to that reported for other tumors [62,63].…”
Section: Discussionsupporting
confidence: 73%
“…The fact that BeWo, a cell line with many characteristics of cytotrophoblast, are almost lacking SR-BI and SR-BI-mediated selective CE-uptake from HDL 3 , supports the assumption that JAr and Jeg3 resembling syncytiotrophoblasts-like properties are suitable in vitro models to study directed cholesterol/CE-transport in polarized cells. Invasiveness of trophoblast cells in vivo and choriocarcinoma cells in vitro apparently is linked to celldifferentiation and proliferation [47] similar to that reported for other tumors [62,63].…”
Section: Discussionsupporting
confidence: 73%
“…Lipoprotein receptor expression and AngII-mediated regulation of lipoprotein metabolism in H295R adrenocortical cells have been studied previously (Martin et al 1999, Cherradi et al 2001, Pilon et al 2003. Cherradi et al (2001) and Pilon et al (2003) reported that AngII stimulated SR-BI, but not LDL receptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cherradi et al (2001) and Pilon et al (2003) reported that AngII stimulated SR-BI, but not LDL receptor expression. Recently, it has been shown that AngII induced uptake of LDL in primary human adrenocortical cells and stimulated aldosterone and cortisol synthesis (Liang et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This translocation process is rapid and implicates a mobilization of intracellular pools, as no significant increase in SR-B1 protein level was observed. This short term regulatory effect seems to be specific to 3T3L1 and primary adipocytes because, in other cell types such as the adrenal gland and the gonads, trophic hormones were reported to stimulate SRB1 expression after 24 h. This was associated with enhanced uptake of HDL-delivered cholesterol esters and steroidogenesis (25,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%